The anatomical relationship of the superficial branches of radial nerve: a cadaveric study - Gupta, Renu; Ghatak, Surajit; Nayyar, Ashish Kumar (International Journal of Research in Medical Sciences, 2024)
Background: The major superficial branches of the radial nerve like inferior lateral cutaneous nerve of arm (ILCNA) and posterior cutaneous nerve of forearm (PCNF) are susceptible to get injured during surgical procedure done in distal half of humerus. Methods: In this study 25 voluntary donated cadavers were dissected to define the course and position ILCNA and PCNF of the radial nerve and their ramifications in relation to anatomical landmarks such as the lateral inter muscular septum or bony landmarks such as lateral epicondyle. Results: The inferior lateral cutaneous nerve of the arm arose from the radial nerve at the lower part of the spiral groove, at a mean of 14.8 cm proximal to the lateral epicondyle and 4.2 cm proximal to the uppermost fibres of the brachioradialis muscle. The posterior cutaneous nerve of the forearm arose from the inferior lateral cutaneous nerve at a mean of 6.7 cm proximal to the lateral epicondyle. Conclusions: The described lateral approach permits assessment of any part of the radial nerve and reduces the risk of iatrogenic injury.